2013
DOI: 10.12659/msm.883791
|View full text |Cite
|
Sign up to set email alerts
|

Couvade Syndrome among Polish expectant fathers

Abstract: BackgroundThe aim of the conducted study was to analyze the phenomenon of Couvade Syndrome amongst fathers expecting their children in Poland. The authors examined the frequency of couvade symptoms in male subjects as well as their associations with male empathy.Material/MethodsThe research involved 143 expectant fathers. All subjects attended antenatal classes, and their female partners were in their third trimester. Before the start of classes, participants were asked to fill in the following questionnaires:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
15
0
3
Order By: Relevance
“…In a study published in 1983, it was concluded that men’s symptoms are a reflection of their level of attachment to the unborn child and involvement in the pregnancy (Weaver & Cranley, 1983). Men who have prepared for their parental role, for example by making antenatal visits, report a higher susceptibility to being afflicted by the syndrome (Kazmierczak et al, 2013). According to attachment theory, the man’s closeness to the fetus gives rise to the syndrome (Cranley, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In a study published in 1983, it was concluded that men’s symptoms are a reflection of their level of attachment to the unborn child and involvement in the pregnancy (Weaver & Cranley, 1983). Men who have prepared for their parental role, for example by making antenatal visits, report a higher susceptibility to being afflicted by the syndrome (Kazmierczak et al, 2013). According to attachment theory, the man’s closeness to the fetus gives rise to the syndrome (Cranley, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In Australian studies from 2010, the principle of at least 8 psychological or physical symptoms was followed [10]. As for the Polish research from 2013, the criteria proposed by Lipkin and Lamb were used [18].…”
Section: Discussionmentioning
confidence: 99%
“…They declared happiness and euphoria, but also concern about their family's future. Kazmierczak et al and Kiełbratowska et al stated that men need the Couvade syndrome to be in the center of the woman's attention and to adjust to the new situation [18,22]. A contemporary man demands the recognition of his place and role during his wife's/partner's pregnancy and labor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors mention changes in sexual habits, fear, anxiety, and curiosity. The symptoms disappear after the wife's delivery [19].…”
Section: Psychology Of Pregnancymentioning
confidence: 99%